1995
DOI: 10.1002/mcs.1220070209
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of silica porous‐layer open‐tubular columns using fused silica capillaries

Abstract: Abstract. We report a simple method for the preparation of silica PLOT columns using fused silica capillaries. In this method, silica particles were suspended in a methylene chloride/pentane solution containing polymethylhydrosiloxane and passed through the capillary tubing. This caused the silica particles to be dynamically coated on the inner wall of the fused silica capillary. The column was dried and heated, which facilitated the simultaneous deactivation and bonding of a uniform mono-layer of porous silic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
5
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…A major challenge is to cast a relatively uniform porous layer on the column, which can provide sufficient retention and sample loading capacity. Several methods have been developed to realize a retentive layer to increase the surface area and phase ratio, e.g., static, dynamic, , and precipitation coating . These procedures usually involve two steps: first a porous silica layer is cast and then the functional group is attached to the prepared layer.…”
mentioning
confidence: 99%
“…A major challenge is to cast a relatively uniform porous layer on the column, which can provide sufficient retention and sample loading capacity. Several methods have been developed to realize a retentive layer to increase the surface area and phase ratio, e.g., static, dynamic, , and precipitation coating . These procedures usually involve two steps: first a porous silica layer is cast and then the functional group is attached to the prepared layer.…”
mentioning
confidence: 99%
“…Unfortunately, the problems are still the same. Open tubular columns with the stationary phase supported on the tubing walls is another way to circumvent the use of particles and the accompanying packing problems . Although open tubular columns were first described nearly three decades ago, they have never become popular in liquid chromatography.…”
mentioning
confidence: 99%
“…It is a relatively straightforward procedure to transfer carrier-free zone electrophoresis and open-tubular chromatography experiments in capillaries to analogous runs in the narrow channels in chips. Many such studies have been reported. However, to achieve uniform packing of such channels with beads for chromatographic experiments seems to be an impossible task, particularly if the channels are not straight but are curved, for instance, into a serpentine configuration. The difficulty of affixing frits to support the bed is obvious.…”
mentioning
confidence: 99%